Integrated STEM activity with 3D printing and entrepreneurship applications. (2nd January 2023) - Pabuçcu Akiş, Aybüke; Demirer, Işıl
Abstract: The study presents an integrated STEM activity involving a 3D printer and entrepreneurial problem solving. The study was conducted with 20 high school students who worked in groups to make their own unique kolonya (a traditional Turkish sanitizer), similar to eau de Cologne. They then designed kolonya bottles using TinkerCad before producing them with a 3D printer. After creating their brand, the groups were encouraged to market their products through product label design and brand advertising. Semi-structured interviews were conducted at the end of the study to get the students' feedback about the activity. The students reported that the activity improved their understanding of chemistry and technological tools. They also wished to attend more STEM activities in their classes because they can make boring classes more enjoyable. The activity presented here was critical in providing teachers with an example of integrating a STEM approach into their lessons and incorporating 3D printing in STEM education. The activity also can help students become entrepreneurial thinkers and understand how chemistry is connected to other disciplines like art, mathematics, or engineering.